The yards between us : a memoir of life, love, and football - Russell, R. K., 1992- (Andscape, 2023)
Told through the people and moments that have shaped him, the first out active NFL player to identify as bisexual shares his story, showing the life-changing power of embracing who you are and fighting to make space so others can do the same.